Social responsibility of university student and institutional educational policies. Recognizing the commitments to society - Severino-González, Pedro; Villalobos-Antúnez, José Vicente; Nataly González-Soto, Nataly Chamali-Duarte, Gonzalo Vergara-Piña, (Opción, 1970)
Social responsibility is an issue that is addressed by various institutions of higher education, which seek to respond to the needs and requirements of each of the stakeholders. That is why this research aims to explore the social responsibilities recognized by students of higher education institutions through a quantitative instrument of self-delivery. Among the results, there are differences in the level of assessment between subgroups. Women recognize that they have greater social responsibilities, and urban residents likewise recognize them more than those in rural areas do. It is important that future research may consider a greater number of sociodemographic variables.